(untitled) (Fiep Bulletin - online, 2015)
Metro-Rio is responsible for the transport of thousand of daily passengers in Rio de Janeiro city and has innumerable trained employees exerting specific functions.The security agent is an employee who plays important role in this system, therefore works in the maintenance of the physical integrity of the individuals and in the preservation of the company installations. Security agent function demands that the employee is with physical aptitude, motor and psychological, preparation for possible eventualities, providing security to the users of the service. So that the security agents of Metro-Rio are able to play they functions fully, created a specific selective process for the function, demanding of the candidate has physical aptitudes necessary to participate of the training process for the funcion. This training process objective improvement the physical capacities aerobic conditioning, force and muscular resistence. Objective:This study had for objective verify the morphology characteristics of the individuals candidates to participate of the training process for the function security agent of Metro-Rio. Methods:The study was descriptive data-collecting, the sample was composed for 106 citizens, masculine sort, with ages between 21 and 36 years. Specific tests for anthropometric evaluation had been used (IMC), to neuromuscular evaluation was used The Abdominal Test, The Arms Force Test and The Horizontal Impulse Test and for cardiorrespiratory evaluation was used The 2400m Cooper Test. Results:The group presented index of corporal mass (IMC) moderately obese.The Abdominal Test and The Force Arms Test had gotten respectively good and average .The Test of Horizontal Impulse was presented to regulate and the 2400m Cooper Test got average classification.Conclusion:The evalueated group performance was satisfactory, since it did not participate of physical activity program. The evaluated citizens had been considered able to initiate the specific training for the function of security agent.